2018
DOI: 10.1039/c8an00788h
|View full text |Cite
|
Sign up to set email alerts
|

A novel, fast and sensitive supercritical fluid chromatography-tandem mass spectrometry (SFC-MS/MS) method for analysis of arachidonic acid metabolites

Abstract: The development of a rapid, sensitive and reliable method for the quantification of bioactive arachidonic acid metabolites (AA-metabolites) in biological samples is quite challenging due to the minute concentration, short half-life and their structural complexity arising from different isomers. In this study, a simple, fast and environmentally friendly supercritical fluid chromatography-tandem mass spectrometry (SFC-MS/MS) method was developed and validated for simultaneous measurement of five (PGD2, PGE2, PGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…The nature of the matrix effect measured by SFC-MS, however, depended upon the employed stationary phase. To our knowledge, no evaluation of the matrix effects on the column employed in this study has been reported, but a method for the analysis of plasma eicosanoids in achiral SFC showed similar signal enhancements …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The nature of the matrix effect measured by SFC-MS, however, depended upon the employed stationary phase. To our knowledge, no evaluation of the matrix effects on the column employed in this study has been reported, but a method for the analysis of plasma eicosanoids in achiral SFC showed similar signal enhancements …”
Section: Resultsmentioning
confidence: 88%
“…To our knowledge, no evaluation of the matrix effects on the column employed in this study has been reported, but a method for the analysis of plasma eicosanoids in achiral SFC showed similar signal enhancements. 23 Recoveries were evaluated at three concentration levels and were 30−120% for all analytes in SFC (average values: 74, 80, and 77%, Table S14) and between 13 and 110% in LC (average values: 83, 75, and 71%, Table S15), where the only species with a recovery of <30% was 11(E)-10-HOME. Recoveries for PhytoPs were calculated only by LC and were acceptable for all species (83−106%).…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Mass spectrometry (MS) has also been applied to SFC for some time. MS has a higher capability for molecule identification than a UV diode-array detector. The mobile phase CO 2 has fewer chemical background signals than the commonly used organic solvents, which is expected to decrease the limit of detection (LOD).…”
mentioning
confidence: 99%
“…Targeted lipidomics methods in SFC-MS have been focused on several classes such as free fatty acids (C18 column, methanol/acetonitrile (50:50, v/v) with 0.1% formic acid) 35 or vitamin E derivatives in vegetable oils (NH2 column, pure ethanol), 27 carotenoids in human plasma (C30 column, pure methanol), eicosanoids in human plasma and cerebrospinal fluid (2picolamine column, MeOH with 0.1% formic acid and 10 mM of ammonium acetate), 36 steroids (2-ethylpyridine column, pure isopropanol), 37 environmental toxins as acetogenins (2ethylpyridine column, pure ethanol). 28 These examples perfectly demonstrate the diversity of stationary phase and co-solvent that are described in the literature and which contrast strongly with HPLC studies that lead mainly to the use of C18 columns and water/acetonitrile gradients.…”
Section: Targeted and Untargeted Lipidomicsmentioning
confidence: 99%